Piezoelectric Shoe Energy Harvesting With IoT Monitoring System - Azizi, Muhammad Izham Fikri; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2022)
This paper focuses on harvesting mechanical energy from human motion as an appealing method of getting clean and sustainable electric energy using wearable piezoelectric shoes. However, the main concern is charging the phone on the leg while walking or jogging will interfere with the user’s activities and no storage or protection system is developed to use piezoelectric electricity efficiently. Thus, in this paper, a piezoelectric shoe energy-harvesting prototype consisting of a battery management system monitored by an Internet of Things (IoT) platform is developed. The developed system is able to charge the battery through a battery protection module while discharging at 5V and 2A to charge a mobile phone. The method of the project uses an Arduino Wemos ESP8266 D1 R2 as a microcontroller to transfer data through IoT with the input from a piezoelectric ceramic sensor. The AC input from the piezoelectric sensor is converted to DC by a bridge rectifier and DC input is smoothed by a capacitor before entering the battery management system. Battery charging time depends on battery capacity and input current from the piezoelectric sensor. It is concluded that the prototype manages to monitor a battery management system through an IoT platform and charge a mobile phone. A further possible attempt needs a fuel-gauge sensor to accurately read the voltage and percentage of the battery while a set of high-quality piezoelectric sensors is needed to charge the battery efficiently.